2008
DOI: 10.1007/s11605-007-0391-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Pancreatic Cancer: Analysis by Stage and Treatment

Abstract: In pancreatic cancer patients, survival and palliation of symptoms should be balanced with social and functional impairment, and for this reason, health-related quality of life measurements could play an important role in the decision-making process. The aim of this work was to evaluate the quality of life and survival in 92 patients with different stages of pancreatic adenocarcinoma who underwent surgical and/or medical interventions. Patients were evaluated with the Functional Assessment of Cancer Therapy qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 41 publications
1
72
1
2
Order By: Relevance
“…Besides, chemotherapy patients suffered depression more easily than those who underwent an operation. A recent study has reported that an improvement in QoL was found in patients with localized disease who underwent surgical resection, while there was a decrease in QoL in advanced disease and among those who underwent chemotherapy or chemoradiation [22]. It is indicated that a probable relationship exists between depression and QoL in pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, chemotherapy patients suffered depression more easily than those who underwent an operation. A recent study has reported that an improvement in QoL was found in patients with localized disease who underwent surgical resection, while there was a decrease in QoL in advanced disease and among those who underwent chemotherapy or chemoradiation [22]. It is indicated that a probable relationship exists between depression and QoL in pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Others have assessed quality of life as a predictor of patient outcomes in a variety of malignancies [3][4][5][6][7][8]. Previous work with pancreatic tumors has demonstrated that quality of life is associated with tumor pathology, stage, resectability, and survival [9][10][11]. Therefore, this begs the question of whether KPS and quality of life are related conceptual constructs measuring the same or similar aspects of the patient's well-being.…”
Section: Introductionmentioning
confidence: 99%
“…37 Both can cause intractable nausea and vomiting, which can be difficult to treat owing to the multiple underlying mechanisms and pathophysiology. Chemotherapy, motility dysfunction, opioids, constipation, anxiety, and cholangitis are other causes of nausea and vomiting in this population.…”
Section: Symptom Managementmentioning
confidence: 99%